Phospholipid bilayers in model membranes and drug delivery systems: from physics to pharmacy - Uhríková D. (Sciendo, 2021)
Lipids spontaneously aggregate in an aqueous environment forming supramolecular structures of various architectures known as liquid crystalline mesophases. Their thermodynamic properties determined by dual polar/apolar nature coupled with the possibility to modulate the structural parameters, phase geometry and stability are challenging for applications in drug delivery systems. We review a few examples of functionality of lipid bilayers.